2020
DOI: 10.1080/1828051x.2020.1740896
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phytase on improving the utilisation of pelleted broiler diets containing olive by-products

Abstract: A feeding trial was run to assess the effect of olive cake (OC) in pelleted diets at 0, 10 and 15% with or without 500 FTU/kg diet of a bacterial E. coli phytase (BECP) for broiler chickens during early growth phase period (7-28 days of age). The experimental set up including six treatments as 3 OC levels  2 supplementations (no enzyme and 500 FTU of BECP). Each treatment was replicated eight times, having five male chickens each. Phytase supplementation significantly increased growth rate and improved produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…Nevertheless, as the outbreak of COVID-19 worldwide, the lack of labors affects the produces of corn and soybean and causes feed deficiency. Therefore, it is important to find alternative sources of carbohydrates while safeguarding the health of animals [1][2][3][4][5]. Because fiber is considered to be an anti-nutritional factor, low-fiber diets were typically used when feeding non-ruminant livestock animals in the past [6].…”
Section: A C C E P T E D a R T I C L E Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, as the outbreak of COVID-19 worldwide, the lack of labors affects the produces of corn and soybean and causes feed deficiency. Therefore, it is important to find alternative sources of carbohydrates while safeguarding the health of animals [1][2][3][4][5]. Because fiber is considered to be an anti-nutritional factor, low-fiber diets were typically used when feeding non-ruminant livestock animals in the past [6].…”
Section: A C C E P T E D a R T I C L E Introductionmentioning
confidence: 99%
“…Cowiesonet al [10] and Hamdi et al [11] indicated that the addition of phytase to feeds can increase the digestion of phosphorus, minerals, and amino acids of broilers and increase broilers' bone strength. In addition, the research group of Attia et al and Al-Harthi et al reported that phytase could improve performance of broiler chickens regardless of phosphorus contents in broiler diet [1][2][3][4][5].…”
Section: A C C E P T E D a R T I C L E Introductionmentioning
confidence: 99%
“…The high fiber content and soluble NSPs in the diet can increase the digestion viscosity when in contact with water, forming gums, which increase the size of the bolus and consequently cause gastric distension, which in turn causes a feeling of satiety in the birds, reducing FI (Oliveira et al, 2012;Al-Harthi et al, 2020). The chemical composition of DRC shows that the cassava byproduct has a high starch content and a high fiber concentration, as also observed by Abrahão et al (2006) and Khempaka et al (2009), justifying the reduction in performance.…”
Section: Discussionmentioning
confidence: 95%
“…The international prices of this feedstuff have increased the costs of poultry production, and therefore, reduced marketing margins. Additionally, due to the high amount of wastes from the agricultural sector and food industry, proper management of these resources and identifying the nutritional value, makes it possible to produce cheap and suitable ingredients for poultry which are not competitive with human food (Al‐Harthi et al., 2019, 2020). Agroindustry wastes from tomato, olive, date and sunflower processing have valuable nutritional characteristics, and could be included in poultry rations to facilitate reducing feeding costs (Seidavi et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By‐products of tomato and olive processing can be supplemented in the diet of broilers up to 10% without detrimental effects on production, while improving the biochemical blood profile of chickens. It was shown olive cake is a valuable ingredient for inclusion in broilers' pelleted diet up to 15% during 7–28 days of age with phytase supplementation (Al‐Harthi et al., 2020). Also Al‐Harthi et al (2019) showed that Prosopis pods meal could be used as an alternative feedstuff for poultry production, specially, in tropical and sub‐tropical regions where feed resources are generally limited.…”
Section: Introductionmentioning
confidence: 99%